Treatment of elderly patients with advanced (M1) gallbladder cancer – Aggressive or conservative? - Bin He; Ti Zhou; Penghua Weng; Haibin Lan (Medicine, 2026)
The optimal treatment strategy for elderly patients with distant metastatic gallbladder cancer (GBC, M1) remains controversial. We extracted data from the Surveillance, Epidemiology, and End Results (SEER) database for 528 elderly patients (aged ≥ 60 years) diagnosed with M1 GBC between 2000 and 2020. Patients were stratified by age (60–69, 70–79, ≥80 years) and treatment received: no surgery or chemotherapy (Group N), surgery alone (Group S), chemotherapy alone (Group C), or surgery combined with chemotherapy (Group B). Kaplan–Meier analysis, multivariate logistic regression, and Cox proportional hazards models were used to identify prognostic factors. In the 60–69 age group, Group B had the longest mean survival (8.94 ± 6.71 months) and the best survival curve. In the 70–79 group, all active treatments were protective, with Group B showing the strongest benefit (HR = 0.16, 95% CI 0.07–0.39, P < .001) and a mean survival of 9.92 ± 5.46 months. In the ≥ 80 group, Group B also yielded the longest mean survival (10.54 ± 9.68 months) with significantly better survival curves. Surgery combined with chemotherapy appears to improve prognosis in elderly M1 GBC patients, particularly in those aged 70–79 years, and should be considered a protective factor. However, the retrospective nature, lack of performance status and detailed treatment data, and small subgroup sizes warrant caution in interpretation.